Identifying the Rules for Identifying Customary International Law. (2014) - Murphy, Sean D.
Abstract : The International Law Commission (ILC) decided in 2012 to add to its agenda a new topic on the "identification of customary international law" and to appoint Sir Michael Wood (United Kingdom) as special rapporteur. That project has reached an important point, with a series of Draft Conclusions having been cleared through the Commission's Drafting Committee, and ready for the Commission's provisional approval (together with commentaries) in 2015. As such, now is a propitious time for governments, international organizations, nongovernmental organizations, scholars, and others to weigh in on the merits of these Draft Conclusions, and additional ones that will be developed in 2015–16.